MAPPING THE GLOBAL SCIENTIFIC LANDSCAPE OF COLORECTAL CANCER AND VITAMIN D3 RESEARCH: A BIBLIOMETRIC ANALYSIS - Muhamad Danian; A. Asyura Maharani; Dewi Yuniasih; Mohammad Tri Yoga Tianotak (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2026)
Background: Colorectal cancer is the third leading cause of cancer-related deaths worldwide, with rising incidence in developing countries. Vitamin D3 has been implicated in colorectal cancer development, regulating cell proliferation, apoptosis, and Wnt/β-catenin signaling. Despite the growing body of literature, a comprehensive bibliometric analysis integrating colorectal cancer and vitamin D3 is still limited, highlighting a need to map research trends and collaboration patterns. Objective: This study aimed to evaluate global research trends, thematic structures, and collaboration networks in colorectal cancer and vitamin D3 research to identify hotspots and gaps. Methods: A quantitative bibliometric analysis was conducted using the Scopus database with the TITLE-ABS-KEY query: (“colorectal cancer” OR “colorectal carcinoma” OR “colorectal neoplasm” OR “colon cancer” OR “rectal cancer”) AND (“vitamin D3” OR cholecalciferol OR “25-hydroxyvitamin D3” OR calcitriol). Publications from 2015–2025 in English, including articles and reviews, were included. Data were analyzed using VOSviewer and Biblioshiny to assess publication trends, country- and author-level output, co-authorship networks, keyword co-occurrence, and thematic evolution. Results: Publication output peaked in 2020–2021, with the United States and China leading contributions. Munoz, A., Bostick, R.M., and Zhang, Y. were the most prolific authors. Keyword analysis revealed two main clusters: molecular mechanisms (VDR, calcitriol, Wnt/β-catenin) and clinical studies (vitamin D3 supplementation, serum concentration, trials). Thematic mapping indicated mature molecular research, active clinical translation, and emerging topics. Conclusion: Colorectal cancer research balances well-established molecular insights with evolving clinical applications. Concentrated output in high-capacity countries and underrepresentation in high-burden regions highlight opportunities for capacity building, international collaboration, and evidence-based prevention strategies.